Zika virus nonstructural protein 5 residue R681 is critical for dimer formation and enzymatic activity - Saw, Wuan-Geok (2021)
Zika virus (ZIKV) relies on its nonstructural protein 5 (NS5) for capping and synthesis of the viral RNA. Recent small-angle X-ray scattering (SAXS) data of recombinant ZIKV NS5 protein showed that it is dimeric in solution. Here, we present insights into the critical residues responsible for its dimer formation. SAXS studies of the engineered ZIKV NS5 mutants revealed that R681A mutation on NS5 (NS5R681A ) disrupts the dimer formation and affects its RNA-dependent RNA polymerase activity as well as the subcellular localization of NS5R681A in mammalian cells. The critical residues involved in the dimer arrangement of ZIKV NS5 are discussed, and the data provide further insights into the diversity of flaviviral NS5 proteins in terms of their propensity for oligomerization.